EFEKTIVITAS STRETCHING ABDOMINAL DALAM PENGURANGAN NYERI AKIBAT DYSMENORRHEA PRIMER PADA REMAJA: Effectiveness of Abdomnal Stretching in Pain reduction Due To Primary Dysmenorrhea in Adolescenst - Dwi Purwantini (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2021)
Background: Abdominal stretching is a stretching that focusing on the part of abdominal muscle (rectus abdominis, internus obliqus, external obliqus). Stretching is successful in reducing dysmenorrhea complaint. The aim of research  to analyse the influence of abdominal stretching on reducing the level of primary dysmenorrhea. Methods: The studied design used was quasi experimental with pre and post control design. Subyek were 40 female physiotherapy student with primary dysmenorrhea devided into two groups. The experimental grup get abdominal stretching 10-15 minutes Results: The result of the researt showed that the control group had a p value = 0.52, which means that Ho is accepted, so the hypothesis states that there is no effect on the decrease in VDS scores. The treatment group p = 0.00 Ho was rejected and Ha was accepted so the hypothesis stated that abdominal atretching had an effect on the impairment of VDS. Conclusion: abdominal stretching was effective in reducing level of primary dysmenorrhea